Bahasa Inggris - Iwan Hermawan; Andewi Suhartini; Nurwadjah Ahmad (Edukasia Islamika, 2021)
It is a requirement for Islamic boarding schools-based Islamic educational institutions to improve themselves and carry out more contemporary reforms. This step must be conducted without ignoring the spirit of pesantren as the place of people who understand and implement religious knowledge in everyday life. These reforms can be related to institutional management in transformative leadership, educational curriculum combining religious and general knowledge, also learning processes in the terms of approaches, models, and learning methods. It can be achieved by developing effective communication among educators, students, and parents. In this study, the authors focus on the problem of reforming learning methods by using the development of effective communication at the Islamic boarding school of Al-Wustho Foundation in Pabuaran Subang which is considered successful. This study aims to provide correct knowledge and information about the important changes in Islamic boarding schools. By using case study and descriptive qualitative approach, the authors try to uncover the occurring phenomena by conducting interviews, observations, and processing documents by interpretating the data to become a unified results. This study revealed that the intended modern learning methods are the refinement and adjustment of classical methods, muhafadzah, riyadhah, and scientific rihlah. The four methods are developed through effective communication to lead to the goals of habituating discipline, healthy living, and worship so that Islamic boarding schools do not lose their spirit to meet the needs of education, development, and society in the religious field.